Determinants of Cancer Early Detection Behaviors:Application of Protection Motivation Theory - Zohreh Rahaei; Fazlolah Ghofranipour; Mohammadali Morowatisharifabad; Eesa Mohammadi (Tabriz University of Medical Sciences, 2015)
Background: Cancer is account for 13% of all deaths around the world and is the third cause of mortality in Iran. More than one third of these cases are pre-ventable and about 33% are curable with early detection. The aim of this study was to determine the predictors of cancer early detection (CED) behaviors ap-plying Protection Motivation Theory (PMT). Methods: In this cross-sectional study, cluster sampling method was employed to recruit 260 individuals of above 20 years old in Yazd, Iran and a researcher designed questionnaire was completed through interviews for each of the respondents. PMT theoretical variables and CED behaviors were the basis of data collection procedure. Results: Participants acquired 64.47% of the protection motivation, 30.97% of the passive and 45.64% of the active behaviors‟ possible scores. Theory con-structs predicted 19.8%, 15.6% and 9.6% of the variations for protection moti-vation, passive and active behavior respectively. Protection motivation was re-sponsible for 3.6% of passive and 8% of active behaviors‟ variations. Conclusion: Considering the scarceness of CED behaviors and the applicability of PMT in predicting these behaviors, utilization of the PMT‟s constructs in any interventional programs to accelerate CED behaviors could be an alternate methodological choice in the cancer control initiatives.